THE LOVE RACKET: DEFINING LOVE AND AGAPEFOR THE LOVE-AND-SCIENCE RESEARCH PROGRAM. - Oord, Thomas Jay (Zygon: Journal of Religion & Science, 2005)
Scholars of religion and science have generated remarkable scholarship in recent years in their explorations of love. Exactly how scholars involved in this budding field believe that love and science should relate and/or be integrated varies greatly. What they share in common is the belief that issues of love are of paramount importance and that the various scientific disciplines—whether natural, social, or religious—must be brought to bear upon how best to understand love. I briefly introduce the emergence of the love-and-science research program and note that scholars have not done well defining what they mean by love. I suggest that the present surge in love scholarship will fail to produce the positive results that it otherwise might if love is not defined well. I provide and defend a definition of love adequate for those doing love-and-science research: To love is to act intentionally, in sympathetic response to others (including God), to promote well-being. To explain better what this simple definition entails, I explore its three main phrases. Love is said to have many forms, but agape is the form to which the love-and-science literature most commonly refers. I comment briefly on the debates about how to best understand agape, noting sixteen different definitions proposed by major scholars. I identify weaknesses in many of them and then offer what I argue is a more adequate definition of agape as intentional response to promote well-being when confronted by that which generates ill-being. In short, agape repays evil with good. While research on love and science requires much more than adequate definitions, I believe that the definitions I proffer can prove useful in furthering the love-and-science research program.